2016
DOI: 10.1039/c6ra13978g
|View full text |Cite
|
Sign up to set email alerts
|

The salt-based catalytic enhancement of CO2 absorption by a tertiary amine medium

Abstract: The rise in atmospheric CO2 levels due to the effects of human activities poses a serious threat to the world's ecosystems because of global warming and climate change. Efficient methods are needed to limit the elevation of CO2 level in the atmosphere. Here, we propose an improved CO2 sequestration method that uses new catalysts, specifically a series of tertiary amine nitrate salts, in an aqueous tertiary amine medium. We synthesized the new catalysts and characterized them by using 1 H and 13 C NMR, single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, previous research efforts on the addition of metal catalysts for CO 2 absorption rate enhancement in the tertiary amine media tended to be less active in highly concentrated amine media. Very recently, our group has shown that the CO 2 absorption rate of the tertiary amine can be improved using tridentate and tetradentate ligand-based metal catalysts. , In addition to that, the salt-based catalytic enhancement of CO 2 hydration rate (0.430 × 10 3 M –1 s –1 ) was also observed . However, the tridentate and tetradentate ligand-based metal catalysts were partially soluble and less active in the concentrated basic-aqueous medium, and the salt-based catalysts were less effective than the metal catalysts.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…However, previous research efforts on the addition of metal catalysts for CO 2 absorption rate enhancement in the tertiary amine media tended to be less active in highly concentrated amine media. Very recently, our group has shown that the CO 2 absorption rate of the tertiary amine can be improved using tridentate and tetradentate ligand-based metal catalysts. , In addition to that, the salt-based catalytic enhancement of CO 2 hydration rate (0.430 × 10 3 M –1 s –1 ) was also observed . However, the tridentate and tetradentate ligand-based metal catalysts were partially soluble and less active in the concentrated basic-aqueous medium, and the salt-based catalysts were less effective than the metal catalysts.…”
Section: Introductionmentioning
confidence: 83%
“…An interesting approach to improve the CO 2 absorption kinetics in tertiary amines is the addition of catalysts. , Carbonic anhydrase (CA) mimics and metal catalysts have been used to improve the CO 2 absorption rates in tertiary amine solvent. The use of metal catalysts in strongly basic media (2.5 M) requires the catalysts to be soluble and highly active. However, previous research efforts on the addition of metal catalysts for CO 2 absorption rate enhancement in the tertiary amine media tended to be less active in highly concentrated amine media.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The burgeoning interest of CO 2 as an energy vector for renewable fuel storage and as a C 1 building block for chemical production has renewed attention on CO 2 hydrogenation into formic acid [1][2][3][4][5][6][7][8]. Formic acid and its salts are used as basic chemicals in various industries [9], and are regarded as a liquid form of hydrogen, which is strongly viewed as an ultimate renewable fuel by the scientific and technological community [10].…”
Section: Introductionmentioning
confidence: 99%